2019
DOI: 10.1039/c8ra09028a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of AuPd nanoparticle-decorated graphene-coated ZnO nanorod arrays with enhanced photoelectrochemical performance and stability

Abstract: AuPd nanoparticle-decorated graphene-coated ZnO nanorod (ZNR) array electrodes (ZNR@Gr/AuPd) were synthesized via electrostatic self-assembly followed by solution reduction methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…2e demonstrated that the adjacent lattice fringes of 0.248 nm which were well indexed to the lattice spacing of (101) plane of ZnO, meanwhile the interplanar distances measured from a single AuPd nanoparticle was 0.230 nm, which corresponded to the mean value of (111) planes of face-centred cubic (fcc) Au and Pd. 46 To further investigate the elemental distribution of Au and Pd in the Au/Pd/ZnO nanoclusters, elemental mappings were collected. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2e demonstrated that the adjacent lattice fringes of 0.248 nm which were well indexed to the lattice spacing of (101) plane of ZnO, meanwhile the interplanar distances measured from a single AuPd nanoparticle was 0.230 nm, which corresponded to the mean value of (111) planes of face-centred cubic (fcc) Au and Pd. 46 To further investigate the elemental distribution of Au and Pd in the Au/Pd/ZnO nanoclusters, elemental mappings were collected. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%